Viral Production in Seawater Filtered Through 0.2-μm Pore-Size Filters: A Hidden Biogeochemical Cycle in a Neglected Realm - Yang, Yanhui; Nagata, Toshi (Frontiers in Microbiology, 2021)
Viral production is a key parameter for assessing virus-mediated biogeochemical cycles. One widely used method for the determination of viral production, called the virus reduction assay, reduces viral abundance, while maintaining bacterial abundance, using 0.2-μm pore-size filters. Viral production is estimated from the increase of viral abundance during incubation. We hypothesized that small-cell-sized bacterial communities can pass through 0.2-μm filters and drive viral production, representing a missing fraction of viral production that is missed by the virus reduction assay. Coastal seawater was filtered through 0.2-μm filters and diluted with virus-free seawater. Viral production in the < 0.2-μm filtrate was estimated from changes in viral abundance determined through flow cytometry. We found that viruses were produced in the < 0.2-μm communities, which were strongly enriched with low nucleic acid content bacteria. Estimated viral production in the < 0.2-μm filtrates accounted for up to 43% of total viral production and 10% of dissolved organic carbon production mediated by viral lysis of bacterial cells. By not considering viral production in these < 0.2-μm communities, the virus reduction assay may underestimate viral production. Virus-bacteria interactions in < 0.2-μm communities may represent a significant and overlooked role of viruses in marine food webs and carbon fluxes.